Knowledge and socio-demographic profile of Anganwadi workers in Mangalagiri rural Integrated Child Development Services project, Guntur - Andey, U. Vinod Venkata Kumar; Budimelli, Swapna; Chebrolu, Kalyan; Swamy, C. Ganapathi; Naresh, J.; Babu, R. Surendra (International Journal Of Community Medicine And Public Health, 2019)
Background: Integrated Child Development Services (ICDS) today represents one of the world’s largest programmes for early childhood development. The Anganwadi workers and Anganwadi Helpers are the grass root level functionaries responsible for delivery of services. Methods: A field based cross sectional observational study was conducted in Mangalagiri rural ICDS project to assess the knowledge levels and the socio-demographic profile of the Anganwadi workers, all the Anganwadi workers who are working in Mangalagiri rural ICDS project area have been included in the study. Results: Out of 212 AWWs, majority of AWWs were from the age group of between 30-49 years; 123 (58%) AWWs have education qualification from 6th class to 10th class standard and 135 (63.7%) workers had an experience of more than 10 years. About 142 (67%) AWWs had a good knowledge assessment score. They had best knowledge about immunization (96.7%), referral services (93.4%), growth monitoring (82.5%), health check-ups (75.1%) and nutrition and health education (70%). AWWs complained problems like infrastructure related, excessive work overload and record maintenance. Conclusions: The majority of the AWWs are in the age group of 30 to 49 years. More than half of them belong to lower middle socio-economic class. Maximum number of workers has experience of 10 years or more. All the AWWs in our study had 50% and above knowledge about Anganwadi services. Best knowledge is seen regarding immunization followed by referral services. Least knowledge is seen regarding supplementary nutrition. Major problems reported were excess work and record maintenance.